Growth Differentiation Factor 7 Prevents Sepsis-Induced Acute Lung Injury in Mice. (22nd December 2022) - Dong, Ping; Zhang, Ying; Liu, Nian; Yang, Jun-Yuan; Wang, Hui-Min; Geng, Qing
Abstract : Objective . Acute lung injury (ALI) is a life-threatening complication during sepsis and contributes to multiple organ failure and high mortality for septic patients. The present study aims to investigate the role and molecular basis of growth differentiation factor 7 (GDF7) in sepsis-induced ALI. Methods . Mice were subcutaneously injected with recombinant mouse GDF7 Protein (rmGDF7) and then intratracheally injected with lipopolysaccharide (LPS) to generate sepsis-induced ALI. Primary peritoneal macrophages were isolated to further evaluate the role and underlying mechanism of GDF7 in vitro. Results . GDF7 was downregulated in LPS-stimulated lung tissues, and rmGDF7 treatment significantly inhibited inflammation and oxidative stress in ALI mice, thereby preventing LPS-induced pulmonary injury and dysfunction. Mechanistically, we found that rmGDF7 activated AMP-activated protein kinase (AMPK), and AMPK inhibition significantly blocked the anti-inflammatory and antioxidant effects of rmGDF7 during LPS-induced ALI. Further findings revealed that rmGDF7 activated AMPK through a downregulated stimulator of interferon gene (STING) in vivo and in vitro. Conclusion . GDF7 prevents LPS-induced inflammatory response, oxidative stress, and ALI by regulating the STING/AMPK pathway. Our findings for the first time identify GDF7 as a potential agent for the treatment of sepsis-induced ALI.